Hardy-type inequalities for integral transforms associated with Jacobi operator - M. Dziri; L. T. Rachdi (International Journal of Mathematics and Mathematical Sciences)
We establish Hardy-type inequalities for the Riemann-Liouville and Weyl transforms associated with the Jacobi operator by using Hardy-type inequalities for a class of integral operators.